Business Feasibility and Strategic Development Analysis of a Non-Formal Educational Institution to Enhance Sustainable Competitive Advantage: A Case Study of Deft Ruang Belajar - Teguh Budianto; Budi Djatmiko (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the management development strategies implemented by the non-formal educational institution Deft Ruang Belajar in enhancing sustainable competitive advantage. The research employed a mixed-methods approach using a sequential explanatory design, integrating both qualitative and quantitative analyses. Qualitative data were collected through observation, interviews, and documentation to examine aspects of strategic management, innovation management, marketing, operations, and human resource management. Meanwhile, quantitative data were analyzed using a business feasibility study approach, which included financial projections, financial ratio analysis, Break-Even Point (BEP), Return on Investment (ROI), Average Rate of Return (ARR), Net Present Value (NPV), Profitability Index (PI), Internal Rate of Return (IRR), and sensitivity analysis. The findings indicate that Deft Ruang Belajar has implemented adaptive management development strategies through service innovation, the utilization of digital technology, strengthening human resources, and optimizing operational and financial management. The financial analysis results demonstrate that the business has a favorable level of profitability, positive cash flow, a relatively short investment payback period, and an investment value that is financially feasible for further development. Furthermore, the sensitivity analysis reveals that the institution possesses a relatively strong level of resilience in responding to changes in market conditions. This study concludes that the integration of strategic management and business feasibility analysis can serve as an effective development model for enhancing the sustainable competitiveness of non-formal educational institutions.